Evaluation of dentists’ knowledge on urgency conduct for avulsed teeth (Acta Scientiarum. Health Sciences, 2019)
The aim of this study was to evaluate the knowledge of dentists in the city of Maringá, State of Paraná, Brazil, relative to the management of avulsed teeth. According to the sample calculation, 96 professionals, who were not specialists in Endodontics or oral and maxillofacial surgery, were selected by random draw. The method chosen for verifying their knowledge was the application of a questionnaire composed of multiple choice questions. The data obtained were analyzed by the Exact Fisher test. Among the results obtained, we point out that the definition of tooth avulsion was correctly answered by 99%; 50% indicated milk; 49% saliva; 40% physiological solution, and 7% water as storage media; 52% would use rigid splinting as a fixation method; and for 72% the ideal time of containment procedures would be 60 days. There was association between the years of experience of the professionals with management of cases of tooth avulsion (p = 0.04555). The authors concluded that the dentists in the city of Maringá, State of Paraná, did not demonstrate good knowledge about the procedures to be adopted for management of avulsed teeth. Misunderstandings were observed relative to the appropriate method of storing the avulsed tooth and the type of splinting procedure most indicated for stabilizing the reimplanted tooth.